Does Competitive Advantage Mediate Innovation Capability and Organizational Ambidexterity-Organizational Performance Relationship? - Indra Muis; Puji Isyanto (Universitas Dharma Wacana, 2022)
This study aims to describe innovation capability, organizational ambidexterity, competitive advantage, and organizational performance and investigate the effects of innovation capability and organizational ambidexterity on organizational performance as mediated by competitive advantage. Owners of small and medium-sized enterprises in Bekasi Municipality, West Java Province, Indonesia are the unit of study. This study employs quantitative methodologies. The research population comprised 2,186 SME businesses registered with the Government Office of Small and Medium Enterprises of Bekasi municipality, West Java Province, Indonesia. The respondents consisted of 100 SME business owners, and the sampling technique was simple random sampling. The analysis of the data using the Partial Least Square approach. The results show that innovation capability and organizational ambidexterity have positive effects on competitive advantage; innovation capability and organizational ambidexterity also have a positive direct impact on organizational performance; competitive advantage mediates the innovation capability and organizational performance relationship and also organizational ambidexterity and organizational performance relationship. SMEs owners must implement innovation capability and organizational ambidexterity to improve their competitive advantage and performance.